OA8 Caring for the family caregiver: working with volunteers to implement and improve a service to enable family caregivers to maintain their own wellbeing. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Cohen, S Robin; Keats, Susan; Cherba, Maria; Allen, Dawn; MacKinnon, Christopher J; Bitzas, Vasiliki; Kogan, Naomi; Penner, Jamie L; Calislar, Monica Parmar; Feindel, Anna; Lapointe, Bernard; Baxter, Sharon; et al.
Abstract : Background: Family caregivers suffer physically, mentally, and spiritually. Community volunteers play an important role in supporting patients at the end of life or former caregivers in bereavement. However, there are no research reports of volunteer services focused on maintaining the wellbeing of end-of-life caregivers. Aim: To have volunteers, a hired volunteer coordinator, health care providers, and researchers implement and formatively evaluate a volunteer service to enable family caregivers to maintain their well being while providing care and subsequent bereavement. This presentation will focus on the volunteers' roles with the project as both agents of change to the service and as support for the caregivers. Method: A qualitative formative evaluation informed by Guba and Lincoln's Fourth Generation Evaluation (1989) participatory design was conducted. Data was collected through individual interviews, focus groups, participant observation during volunteer support meetings, and through volunteers' written reflections. Results: Amongst the volunteers, volunteer coordinator, and principal investigator, there was mutual respect for and interest in learning about everyone's roles and experiences in the project. The experience was rewarding because they felt they helped the family caregiver and enjoyed developing and improving the service and working in a supportive team. Volunteers' challenges included being nervous for their first meeting with a caregiver, and frustration with some rules put in place to protect them (e.g. not helping the caregiver with direct care for the patient). Conclusion: Volunteers can be an effective part of the research team, while providing valuable support and encouragement for family caregivers to maintain their own wellbeing.